2018
DOI: 10.1007/s00464-018-6153-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of a new full-thickness endoscopic plication device (GERDx™) for patients with GERD: results of a prospective trial

Abstract: BackgroundPrevious studies suggest clinical effectiveness of endoscopic full-thickness plication in selected patients with gastroesophageal reflux disease (GERD). The aim of this study was to assess the clinical safety and efficiency of the GERDx™ device by evaluating clinical parameters, reflux symptom scores, and quality of life (QoL).MethodsProspective one-arm trial evaluating the outcome of forty patients with GERD subjected to endoscopic plication with the GERDx™ device. We included patients with at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…A previous prospective single-arm study had reported positive results on the efficacy of the GERD-X device for the treatment of patients with GERD on PPIs and refractory GERD. 12 However, randomised trials and long-term follow-up data are needed to determine the efficacy and safety of the device in treating patients with GERD. The objective of this single-centre, randomised, sham-control trial was to determine the efficacy and safety of EFTP (GERD-X) in patients with PPI-dependent GERD, compared with the sham procedure, in improving the health-related quality of life (GERD-HRQL), GERD symptoms and oesophageal acid exposure.…”
Section: Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…A previous prospective single-arm study had reported positive results on the efficacy of the GERD-X device for the treatment of patients with GERD on PPIs and refractory GERD. 12 However, randomised trials and long-term follow-up data are needed to determine the efficacy and safety of the device in treating patients with GERD. The objective of this single-centre, randomised, sham-control trial was to determine the efficacy and safety of EFTP (GERD-X) in patients with PPI-dependent GERD, compared with the sham procedure, in improving the health-related quality of life (GERD-HRQL), GERD symptoms and oesophageal acid exposure.…”
Section: Endoscopymentioning
confidence: 99%
“…The arms were closed, and as per the study protocol 2 pre-tied transmural pledget sutures were deployed to ensure full-thickness plication and tight closure of gastro-oesophageal junction around the device. 12 The EFTP system and the ultraslim endoscope were then straightened, removed and the gastroscope was reintroduced to evaluate the post plication gastro-oesophageal junction. No retreatments were allowed.…”
Section: Randomisation and Interventionmentioning
confidence: 99%
“…Im Laufe der letzten 15-20 Jahre wurden zusätzlich endoskopische Verfahren entwickelt, die zu einem kompetenten Ventilmechanismus führen sollten. [23].…”
Section: Aktueller Stand Bei Den Endoskopischen Therapieverfahren Der Gerd (Endoplikation): Gerdx Muse Esophyxunclassified
“…His Hb normalized and was clinically better. GERDx™ has been used to treat reflux‐related symptoms with promising results in GERD . To the best of our knowledge, this is the first unusual complication of the GERDx procedure.…”
mentioning
confidence: 99%